Differential Hepatic Expression of miRNA in Response to Aflatoxin B1 Challenge in Domestic and Wild Turkeys - Kade Jorud; Kristelle M. Mendoza; Thomas Kono; Roger A. Coulombe; Kent M. Reed (Toxins)
Aflatoxin B1 (AFB1) is a major foodborne mycotoxin that poses a significant economic risk to poultry due to a greater degree of susceptibility compared to other agricultural species. Domesticated turkeys (Meleagris gallopavo) are especially sensitive to AFB1; however, wild turkeys (M. g. silvestris) are more resistant. A lack of functional isoforms of hepatic glutathione S-transferases (GSTs), an enzyme that plays a role in the detoxification of aflatoxin, is suspected as the reason for the increased sensitivity. Previous studies comparing the gene expression of domesticated and wild turkeys exposed to AFB1 identified hepatic genes responding differentially to AFB1, but could not fully explain the difference in response. The current study examined differences in the expression of microRNAs (miRNAs) in the livers of wild and domesticated turkeys fed dietary AFB1 (320 μg/kg in feed). Short-read RNA sequencing and expression analysis examined both domesticated and wild turkeys exposed to AFB1 compared to controls. A total of 25 miRNAs was identified as being significantly differentially expressed (DEM) in pairwise comparisons. The majority of these have mammalian orthologs with known dysregulation in liver disease. The largest number of DEMs occurred between controls, suggesting an underlying difference in liver potential. Sequences of the DEMs were used to identify potential miRNA binding sites in target genes, resulting in an average of 4302 predicted target sites per DEM. These DEMs and gene targets provide hypotheses for future investigations into the role of miRNAs in AFB1 resistance.